(untitled) (Papeles, 2012)
The papermakes a proposalof therole of the teacher-researcher determined by theconceptual and proceduralframeworkof formative researchthatwants to enter thenuclearaspectsofthe research processdevelopedby teachersof the Facultyof Technologyofthe University Distrital Francisco José de Caldas. Understoodformative researchas a processof action-transformation, analyzes the role of teachersinfluenced by theunderstandingbetweenscientific research andteaching practice. It pointsto a roledemarcated bythe wayyou should assumeinteachingUniversityresearchandresearch-related education.